(untitled) (e-Journal of Linguistics, 2023)
The widespread use of English is depicted in the Linguistic Landscape (LL) in Tulungagung competes the Indonesian language (the national language) and Javanese language (the local language). The present study is aimed (1) to view the position of English language among the existing languages, (2) to investigate what motive that urges a signage owner in acquiring English, and (3) to explain the role performed by English in society. A descriptive qualitative method in research is carried out to explain the phenomenon. Data were collected from an observation of languages appear on signage and an interview to the signage owner. This study is set up in Tulungagung Regency that characterized as the Central Business District (CBD). From the total 460 photographed signages observed and the interviews done, it is shown that English in society is not more dominant than the Indonesian language in use as explained by Landry & Bourhis (1997) but as the interviews done with the signage owner, it narrates that English carries some characterization proposed by Piller (2001) that urge a party to acquire English and it also plays significant roles in society, specifically in business field as stated by Lee (2019). Thus, it challenges the use of local language, the Javanese language, since English appears within its excellence.